Fungal agents in different anatomical sites in Public Health Services in Cuiabá, state of Mato Grosso, Brazil - Araújo, Sebastião Martins de; Fontes, Cor Jésus Fernandes; Leite Júnior, Diniz Pereira; Hahn, Rosane Christine (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
INTRODUCTION: A contribution to the regional epidemiological profile of the most common fungal agents in Public Health Services in Cuiabá, state of Mato Grosso, including university hospitals and polyclinics. METHODS: Clinical specimens (n = 1,496) from 1,078 patients were collected, submitted to direct mycological exam (potash or stick tape method) and cultured in specific mediums. Dermatophytic and non-dermatophytic agents were identified according to micromorphology (Ridell technique). RESULTS: The majority of the 1,496 specimens were skin (n = 985) and nail exams (n = 472). Of the 800 positive cultures, 246 (30.8%) corresponded to dermatophytes and 336 (42%) to yeasts of the genus Candida, 190 (23.7%) to other yeasts, 27 (3.4%) to non-dermatophytic filamentous fungi and one (0.1%) the agent of subcutaneous mycosis. Lesions considered primary occurred in greater numbers (59.5%) than recurrent lesions (37.4%), with a greater concentration of positivity occurring on the arms and legs. CONCLUSIONS: Comorbidities, allergies and diabetes mellitus were conditions associated with greater positivity in direct mycological exams and cultures. Positive culture was considered a definitive diagnosis of fungal infection and confirmed 47.8% of diagnostic hypotheses.